Research on VHF Band Signal Modulation Classification and Recognition Methods Based on Algorithm of First-Order Cyclic Moment - Faquan Yang; Zan Li; Zhongliang Luo (Dianxin kexue)
In view of the problem of modulation recognition algorithm existing about low recognition rate under environment condition of low SNR，the algorithm of first-order cyclic moment was first presented used in band signal of VHF modulation classification recognition.The first-order cycle frequencies at which estimated first-order cyclic moment magnitudes exceed the cut-off value were selected as candidate cycle frequencies based on estimation first-order cyclic moment at first-order cycle frequency series，then decided to choose the number of candidate cycle frequency by a cyclostationarity test to realize signal modulation classification recognition.The classification recognition rate can reach more than 98% under condition of SNR is greater than -6 dB.